Moral Bioenhancement for Social Welfare: Are Civic Institutions Ready? - Shook, John R.; Giordano, James J. (Frontiers in Sociology, 2017)
Positive assessments of moral enhancement too often isolate intuitive notions about its benefits apart from the relevance of surrounding society or civic institutions. If moral bioenhancement should benefit both oneself and others, it cannot be conducted apart from the enhancement of local social conditions, or the preparedness of civic institutions. Neither of those considerations have been adequately incorporated into typical neuroethical assessments of ambitious plans for moral bioenhancement. Enhancing a person to be far less aggressive and violent than an average person, what we label as “civil enhancement,” seems to be quite moral, its real-world social consequences are hardly predictable. A hypothetical case about how the criminal justice system would treat an offender who already received civil enhancement serves to illustrate how civic institutions are unprepared for moral enhancement.